The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/nrd2194
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells as a source of models for drug discovery

Abstract: Embryonic stem cells (ESCs) will become a source of models for a wide range of adult differentiated cells, providing that reliable protocols for directed differentiation can be established. Stem-cell technology has the potential to revolutionize drug discovery, making models available for primary screens, secondary pharmacology, safety pharmacology, metabolic profiling and toxicity evaluation. Models of differentiated cells that are derived from mouse ESCs are already in use in drug discovery, and are beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 138 publications
0
98
0
3
Order By: Relevance
“…Following blasticidin selection, cultures were maintained in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum for the duration of the cultures. On days 0, 3,7,10,14,20,28,35,45,60,90, and 120, approximately 3 million cells were removed for RNA collection. The differentiation protocol and sample collection were performed in 3 independent replicates as indicated by Run 1, 2, and 3 in Figs.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following blasticidin selection, cultures were maintained in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum for the duration of the cultures. On days 0, 3,7,10,14,20,28,35,45,60,90, and 120, approximately 3 million cells were removed for RNA collection. The differentiation protocol and sample collection were performed in 3 independent replicates as indicated by Run 1, 2, and 3 in Figs.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
“…In this light, a major advantage of hiPSCderived tissues over primary tissue is their ability to maintain functional properties in vitro and to be reproducibly expanded to produce tissue from a defined genetic background. These properties, and their ability to differentiate into any adult tissue, make hiPSCs an attractive therapeutic target for tissue replacement therapies, and as an in vitro system for drug development and discovery [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Concernant la culture des cellules, les protocoles d'amplification et de différenciation devront être standardisés. Cela implique d'éviter les systèmes de coculture, de travailler en milieu défini et avec des techniques de dissociation adaptées, tout en veillant à ne pas induire d'instabilité génétique [28]. Ces mêmes protocoles devront être compatibles avec un changement d'échelle, ce qui nécessite une automatisation des processus par des plates-formes robotiques [29] ou le recours à des bioréacteurs [30,31] (➜).…”
Section: Innovations Technologiques Indispensables Pour L'utilisationunclassified
“…Of the 30 studies identified, 28 used immortalised cell lines derived from human neuroblastomas. These cells are not ideal models to study ischaemic stroke because of their ability to survive under hypoxic conditions and possession of abnormal karyotypes, which leads to constant cell division (not a feature of normal neurons) [15]. The remaining two studies took a more relevant but less practical approach of examining human slice preparations subject to oxygen-glucose deprivation.…”
mentioning
confidence: 99%
“…Thus, while they may ultimately be important tools for exploring the impact of an individual's genetic background on risk of stroke and may allow personalised medicine in less time-constrained diseases, they offer little advantage as an initial screening tool. Conversely, ES cells can be maintained in culture for a large number of passages and can easily be differentiated towards a range of different cell types [15]. This is important because high-throughput screening will be most effective when all of the cell types which might contribute to a disease are available.…”
mentioning
confidence: 99%